1991
DOI: 10.1042/bj2800179
|View full text |Cite
|
Sign up to set email alerts
|

Postnatal changes in sialylation of glycoproteins in rat liver

Abstract: Glycoproteins containing N-linked oligosaccharides were prepared from plasma and liver microsomes of rats aged 0-5 weeks, and galactose and sialic acid content were determined. The sialic acid/galactose ratios in plasma membrane N-glycans remained at about 1 throughout the postnatal period, suggesting that most of the galactose residues are sialylated. In the same way, it was suggested that most of the galactose residues of microsomal N-glycans were sialylated at 0, 4 and 5 weeks of age, but that the degree of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…We found that plasma VN obtained from PH rats had low carbohydrate concentrations, suggesting that PH-VN was less glycosylated (15). The decreased N-glycosylation of VN at 24 h after partial hepatectomy could be attributed to the attenuation of the oligosaccharide transferase activity in microsomes (31,32), which also causes the decrease of total glycoprotein synthesis in regenerating liver (33). In the early stage after partial hepatectomy, amounts of several kinds of fucosylated glycoprotein were reported to increase (34).…”
Section: Discussionmentioning
confidence: 82%
“…We found that plasma VN obtained from PH rats had low carbohydrate concentrations, suggesting that PH-VN was less glycosylated (15). The decreased N-glycosylation of VN at 24 h after partial hepatectomy could be attributed to the attenuation of the oligosaccharide transferase activity in microsomes (31,32), which also causes the decrease of total glycoprotein synthesis in regenerating liver (33). In the early stage after partial hepatectomy, amounts of several kinds of fucosylated glycoprotein were reported to increase (34).…”
Section: Discussionmentioning
confidence: 82%
“…It has been shown that SA residues which occupy terminal positions in N-linked oligosaccharides of glycoproteins play important roles in various biological functions (Oda-Tamai et al 1991). Desialylation shows its effect not only by altering the structure and function of glycoproteins, but also by increasing the amount of free SA levels which leads to emergence of pathologies in tissues (Goswami and Koner 2002).…”
Section: Discussionmentioning
confidence: 99%
“…1B) revealed no mutation in the NTCP glycosylation site, the lack of N-linked glycosylation cannot be explained by NTCP itself. Enzymes involved in protein glycosylation, such as galactosyl transferase and sialyl transferase, undergo ontogenic regulation (22,23). Rat NTCP produced in the first 4 weeks of life was underglycosylated as a 39-kDa species rather than the 50-kDa species found in adult liver, with both species converted to a 33-kDa form following treatment with N-glycanase (24).…”
Section: Discussionmentioning
confidence: 99%